Workshop Theatre in South Africa in the 1980s : a critical examination with specific reference to power, orality and the carnivalesque - Fleishman, Mark (Department of Drama, 2015)
This study attempts to critically examine the form of theatre practice which in South Africa has become known as workshop theatre focussing on the period of the 1980s. It examines the history of the form; the process by which it is made; and the kinds of plays it produces. The examination is centered around three philosophical concepts: discourse and power as understood within poststructuralist critical theory; orality and the oral tradition; and the carnivalesque as it is conceived of in the writing of Mikhail Bakhtin. Chapter One is a general introduction to the dissertation. In Part I of the study, it is argued that workshop theatre forms part of a power struggle within the field of theatre practice in South Africa because it is essentially an oral form. Chapter Two describes the rise of authorship within the European theatre practice in the seventeenth century resulting in the marginalisation of the improvisatory 'carnival' tradition, and suggests that it was this literary tradition of theatre practice that was imported to South Africa as part of the British colonial project. Chapter Three examines the indigenous oral performance forms that pre-existed the arrival of the literary theatre in southern Africa with particular reference to the Nguni oral narrative. Similarities are indicated between these oral forms of performance and the carnivalesque forms of the European tradition. Chapter Four traces the gradual involvement of members of the non-hegemonic group in theatre practice in South Africa from a predominantly literary practice limited to a select few participants to oppositional practice involving larger numbers across a wide range of social contexts. It is argued that workshop theatre facilitated this movement because it is an essentially oral form and incorporates popular carnival elements first introduced in the theatre of Gibson Kente. Part II of the study it is argued that workshop theatre is itself a site of numerous power struggles. Chapter Five examines the workshop process with specific reference to the role of improvisation. It is argued that improvisation potentially frees the performer to participate in the meaning-making process but that the extent of this participation is limited by struggles for power within the workshop group. Chapter Six examines the product of the workshop. It is argued that there is a dominant form of workshop play produced in the 1980s and that this form displays many oral and carnivalesque elements. It is further argued that there are movements away from this dominant form towards more literary forms and styles as a result of changes in the make-up of the workshop group and its relationships of power. In Chapter Seven the conclusion is drawn that workshop theatre reflects the current struggles within the South African social and political body, and that it continues to be a relevant form of theatre practice in South Africa because it diffuses strong centres of authorial power and presents possibilities for radical participatory democracy.